Effect of Deformation during Stamping on Structure and Property Evolution in 3rd Generation AHSS - Branagan, Daniel; Parsons, Craig; Machrowicz, Tad; Cischke, Jonathon; Frerichs, Andrew; Meacham, Brian; Cheng, Sheng; Justice, Grant; Sergueeva, Alla (Scientific Research, 2018)
Over the past decade extensive development of advanced high strength steel (AHSS) was driven by the demand from the automotive industry for stronger materials that can enable lightweighting to meet increasing fuel efficiency requirements. However, achievement of higher strength in many AHSS grades comes with reductions in ductility, leading to geometric constraints on formability and limiting their application. In this paper, a 3rd Generation AHSS with a compelling property combination of high tensile strength of ~1200 MPa and total elongation > 40% was used for laboratory and stamping studies. Various auto related laboratory tests were done including tensile testing, 180 degree bending, bulge testing, and cup drawing to estimate the steel’s formability under different applied conditions. Additionally, since laboratory testing provides only an estimation of the potential stamping response, the 3rd Generation AHSS sheet was stamped into B-pillars under industrial stamping conditions. Non-destructive and destructive analysis of the resulting stampings were done to evaluate the microstructural and property changes occurring during stamping. Significant strengthening of material in the stamped part is attributed to the structural changes through the complex Nanophase Refinement and Strengthening mechanism.
Keywords: Steel; Advanced High Strength Steel; Cold Formability; Stamping; Structure; Properties